Repair of local damages to precast prestressed slab elements at a parking garage - Lutomirska Marta (EDP Sciences, 2021)
The durability of precast structures often depends on quality of execution of the connections between the structural elements. Essential also is their design and proper exploitation. This paper focuses on the magnitude of damages as well as repair methods used for a precast slab, which consists of prestressed double T slab elements supported on prestressed inverted T girders. It was found that during execution, the girders were forced to fit dowel bars, which resulted in their initial deformation. Moreover, those connection zones were subjected to unpredicted loading coming from delivery trucks. It resulted in crushing of the elastomeric bearings, uncontrolled rotation of double T precast elements, and further deformation of dowel bars. Numerous cracks, splits, concrete spalling, surface rust stains, and efflorescence were observed. To prevent failure, a project for repair was developed. The slab was lifted with the use of a jacks to provide necessary space for work. Damaged dowel bars and elastomeric bearings were removed. The concrete surface of double T beams and the inverted T girder was cleaned, refilled, prepared, and strengthened with FRP wraps. Additionally, steel angles were used to protect the edges of the inverted T girder.